2013
DOI: 10.1038/cdd.2013.83
|View full text |Cite
|
Sign up to set email alerts
|

The Hippo pathway kinase Lats2 prevents DNA damage-induced apoptosis through inhibition of the tyrosine kinase c-Abl

Abstract: The Hippo pathway is an evolutionarily conserved pathway that controls cell proliferation, organ size, tissue regeneration and stem cell self-renewal. Here we show that it also regulates the DNA damage response. At high cell density, when the Hippo pathway is active, DNA damage-induced apoptosis and the activation of the tyrosine kinase c-Abl were suppressed. At low cell density, overexpression of the Hippo pathway kinase large tumor suppressor 2 (Lats2) inhibited c-Abl activity. This led to reduced phosphoryl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
63
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(69 citation statements)
references
References 58 publications
3
63
0
1
Order By: Relevance
“…In crowded cells, where the Hippo pathway is functional, activated Lats phosphorylates c-Abl to downregulate its kinase activity, 32 suggesting the domination of Hippo over the DNA damage pathway. Hippo pathway cross-talks with other signaling pathways to orchestrate cell-fate decisions was lately reinforced in studies outlining the connection of Hippo components with the PI(3)K-mTOR pathway, Wnt/β-catenin pathway, and mechanotransduction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In crowded cells, where the Hippo pathway is functional, activated Lats phosphorylates c-Abl to downregulate its kinase activity, 32 suggesting the domination of Hippo over the DNA damage pathway. Hippo pathway cross-talks with other signaling pathways to orchestrate cell-fate decisions was lately reinforced in studies outlining the connection of Hippo components with the PI(3)K-mTOR pathway, Wnt/β-catenin pathway, and mechanotransduction.…”
Section: Discussionmentioning
confidence: 99%
“…pCDNA c-Abl Δ1-81 and pCDNA c-Abl Δ1-81 K290H (kinase dead) have been previously described. 32 PCDNA3-HA-TEAD1 was cloned from pPGS-3HA-TEAD1, kindly provided by KL Guan (Addgene, Cambridge, MA, USA; plasmid no. 33050).…”
Section: Methodsmentioning
confidence: 99%
“…Finally, overexpression of mutant c-Abl constructs, which lack LATS2 phosphosite or harbor a point mutation in SH3 domain, overcame LATS2 inhibition and resulted in apoptosis in densely plated cells upon DNA damage. Taken together, these observations by Reuven et al 1 suggest that when DNA damage is induced in dense cells, activated LATS2 binds and inhibits c-Abl-mediating phosphorylation of p73Y99 and YAPY357, resulting in reduced apoptosis and cytoprotection (Figure 1). Importantly, under these conditions, LATS2 can also bind and phosphorylate YAP at S127, resulting in its cytoplasmic sequestration, thus YAP becomes unable to bind and coactivate p73 to enhance its apoptotic function.…”
mentioning
confidence: 63%
“…In this issue of CDD, Reuven et al 1 provide an elegant mechanism by which LATS2, a core component of the Hippo pathway, impedes DNA damage-induced apoptosis through inhibition of c-Abl. By dissecting signaling events upon g-irradiation of sparse and dense cell, the authors revealed a dialogue between Hippo signaling members and DNA damage response (DDR) proteins.…”
mentioning
confidence: 99%
See 1 more Smart Citation